(untitled) (JURNAL PROTEKSI KESEHATAN, 2024)
Nause vomiting is one of the physiological changes in first trimester of pregnant woman due increased of human chorionic gonandotropin (HCG) produced by placenta. Symptoms of nausea vomiting usually occur 6 weeks after the first day of last menstrual period and approximately 10 weeks. Purpose of research was to see relationship between parity and work on the incidence of nausea vomiting in the Payung Sekaki Health Center Area. Type of research is quantitative analytic with cross sectional. The sampling technique was accidental sampling 46 people. Data processing bivariate analysis using chi-square test. The results of statistical test that there is relationship between parity with pvalue 0.001 and work with pvalue 0.0004 on the incidence of nausea vomiting in pregnant women. The concluded that is a significant relationship between parity and work on the incidence of nausea ang vomiting in pregnant woman in the Payung Sekaki Health Center Area with pvalue<0.05.